Kode Etik Akuntan Publik Dan Pelanggaran Pelaporan Audit PT Garuda Indonesia Tbk - Fitrah Sarah Maryanti; Kasmanto Miharja; Anastasya Amara Salsabila; Yunita Tri Damayanti (Pusat Riset dan Inovasi Nasional, 2024)
This study analyzes the Code of Ethics for Public Accountants and Audit Reporting Violations of PT Garuda Indonesia Tbk. This research uses a qualitative descriptive method. The data collection technique in this research uses literature review. The result of this study is that based on the violation case that occurred at PT Garuda Indonesia, it appears that a public accountant ignores the ethical values of the profession which should be a guide and guideline in carrying out his duties. The auditor who allowed the recognition of receivables as Garuda’s revenue showed this imprudence. The KAP violated various auditing standards in this case showing that he was not professional in his work. This case lowers public confidence in the accounting profession, which should be responsible for the management of accounting information.